Real-world evidence of characteristics and factors influencing herbal medicine use for weight loss in adults - Lee, Boram; Yang, Changsop; Yim, Mi Hong (Frontiers in Pharmacology, 2024)
Background: Obesity imposes a significant socioeconomic burden owing to its high prevalence. In response to the adverse outcomes associated with conventional pharmacotherapy and the challenges of low adherence to lifestyle interventions, herbal medicine has surfaced as an actively utilized approach for weight loss. Therefore, this study aimed to analyze the characteristics and influencing factors of herbal medicine users for weight loss in adults.Methods: Overall, 22,080 participants were included based on data from the Korea National Health and Nutrition Examination Survey from 2010 to 2019. Simple logistic regression analyses were used to derive the associations between herbal medicine use for weight loss and individual characteristics. Three models were constructed utilizing multiple logistic regression analyses to assess the associations between herbal medicine use for weight loss and the combined characteristics of predisposing, enabling, and need factors according to Andersen's model.In the full adjustment model, women, younger adults, those with higher incomes, and individuals reporting higher levels of perceived stress were more prone to use herbal medicine for weight loss in the past year. Adults who identified body image as being fat/very fat, those who consumed alcohol, and those classified as severely obese by BMI were also more prone to use herbal medicine for weight loss. In particular, adults with a higher rate and amount of weight loss in the past year were more likely to use herbal medicine for weight loss compared to those experiencing weight gain/no changes/loss of 0-3 kg.Our study was the first to derive the characteristics and influencing factors of herbal medicine users for weight loss among adults. These findings hold significant promise for informing future research endeavors and policy decision-making for effective resource distribution for obesity treatment.